Swastika - Mora, Philippe; Becker, Lutz (Umbrella Entertainment, 2006)
Employing archival footage from the Nazi era to reveal the workings behind Hitler's monster regime, this acclaimed and groundbreaking feature-length documentary has remained virtually unseen since its release in 1973. Produced by Lord David Puttnam and Sanford Lieberson and directed by Australian filmmaker Phillipe Mora, "Swastika" utilizes an incredible body of archival footage to chronicle the daily lives of Germans under Hitler. Combining German newsreels and other propaganda footage looted at the war's end with rare colour home movie footage shot by Eva Braun - that presented for the first time Hitler's banal home life - "Swastika" provides the definitive look at the man who became known as the personification of evil. [www.umbrellaent.com.au]